A development framework for component-based agent-oriented business services. (6th March 2009) - Nguyen, Tai; Kolp, Manuel; Penserini, Loris
Nowadays, modern applications tend to be open and dynamic since they evolve in a changing organisational and operational environment where components can be added, modified, or removed at any time. Together, service-oriented computing and Multi-Agent Systems (MASs) represent dynamic and evolving structures which can change at run-time to benefit from the capabilities of new system entities or replace obsolete ones. They are particularly useful to define business services that refer to specific electronic business interactions. In this paper, we propose a business service development framework composed of three phases: modelling, design and specification. The modelling phase models two levels of a business service: the services of a business service and the agents of each service. The design phase details a business service with three models: component, structural and interaction. In the interaction model, which expresses the exchange or the communication between services or agents of a business service, there are three levels to model: the component (between services), the agent (between agents) and the message (the structure and ontology of messages). Finally, the specification phase presents information acquired from the modelling and design phases in a machine-readable language. Using the support toolkit, we developed a Multi-criteria Data Integration case study to illustrate the framework application.